France and the Cult of the Sacred Heart : An Epic Tale for Modern Times - Jonas, Raymond Anthony (Book collections on Project MUSE., 2000)
The story of the church of the Sacred Heart in Paris, a monument to French Catholicism and national identity, is told in this text, focusing on key moments in its development and drawing on archival sources encompassing French politics and history.